Three essays on personality characteristics and financial satisfaction - Tharp, Derek T. (Kansas State University, 2017)
Little is known about the relationships between personality characteristics and financial satisfaction. This dissertation examines three questions. First, what are the relationships between personality characteristics and financial satisfaction at the American state level? Second, what are the relationships between personality characteristics and financial satisfaction at the individual level? Third, what are the relationships between personality characteristics and financial satisfaction among financially strained households? Essay one utilizes data aggregated at the state level from two nationally representative datasets in order to examine the relationships between Big Five personality traits (openness to experience, conscientiousness, extraversion, agreeableness, and neuroticism) and financial satisfaction at the American state level. Results from bivariate analyses and a two-block hierarchical regression model indicate that conscientiousness is negatively associated with financial satisfaction and extraversion is positively associated with financial satisfaction at the American state level. Essay two utilizes data from the 2012 wave of the Health and Retirement Study (HRS) to examine relationships between personality characteristics (Big Five personality traits and positive/negative affect) and financial satisfaction at the individual level. Results from a three-block ordinal logistic regression model indicate that personality characteristics are important predictors of financial satisfaction. Extraversion is positively associated with financial satisfaction while neuroticism and agreeableness are negatively associated with financial satisfaction when Big Five personality traits were the only personality characteristics incorporated into the model. However, when positive affect and negative affect were added to the model, only agreeableness remained negatively associated with financial satisfaction, while both positive and negative affect were positively and negatively associated with financial satisfaction, respectively. Essay three utilizes data from the 2012 wave of the HRS to examine relationships between personality characteristics (Big Five personality traits and positive/negative affect) and financial satisfaction among individuals in households exhibiting both objective and subjective indicators of financial strain. Results from a series of ordinal logistic regressions indicate that individual level associations between personality characteristics and financial satisfaction remained largely the same among households exhibiting financial strain, though evidence suggests that interventions aimed at influencing positive affect may be an effective means to enhancing well-being among financially strained populations. Overall, personality characteristics were found to be important predictors of financial satisfaction which have been largely overlooked in prior models of financial satisfaction. Going forward, a better understanding of the relationships between personality characteristics and subjective measures of economic well-being will be needed in order to determine how consumer well-being can be most effectively promoted.
Keywords: Financial satisfaction; Personality; Big Five; Affect